(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The rapid change in economic is a serious challenge facing all countries around the world, even developed ones. This challenge is increasing as the world enters the age of knowledge in which different knowledge and technologies have emerged and the distance between the emergence of scientific knowledge and its actual application on the ground has been reduced as well as the growing role of science and technology in community development. One of the most important technology amongst these technologies is nanotechnology, where this technology plays a major role in the development of products and modern devices and reduces cost with quality improvement. This technology is cross-cultural, requires a comprehensive knowledge structure and depends on continuous education and financial support. For that, Iraqi technological universities need to play new roles to align with the requirements of the era through the transfer and resettlement of the experience of international universities and prestigious and well-known in this area such as the University Technology PETRONAS (UTP), Malaysia, with a comprehensive understanding of the experience and the use of consultants from that university experience. The research shows the serious orientation of UTP in pushing the process of continuous improvement and development of the product in terms of quality, size, weight and cost. The efforts of UTP have also resulted in many awards and two patents in manufacturing methods. In this research, however, we propose to Iraqi technical universities to adopt a new research method that simulates modern research methodologies such as the one followed UTP university to obtain results that meet the customer satisfaction (students, teachers and society) throughout self-evaluation, goals setting, designing the objectives of the educational process along with effective leadership in the process of continuous improvement.